The Effect of Occupational Safety and TKBM Competence on Performance and Its Implications on Loading and Unloading Productivity at Tanjung Priok Port - Utama, Yusuf Pria; Rini Setiyawati (Dinasti International Journal of Digital Business Management, 2024)
Loading and unloading productivity problems at Tanjung Priok Port such as congestion, long waiting times, and lack of efficiency in the loading and unloading process can hinder port productivity. The formulation and objectives of this study are to determine and analyze the effect of work safety and TKBM competence on loading and unloading productivity mediated by loading and unloading performance at Tanjung Priok Port. This research design uses a cross sectional design. The type of data used with primary and secondary data. The population in this study were users of port services at Tanjung Priok Port. With a sample of 60 service users at Tanjung Priok Port. The analytical tool used is SmartPLS software. The results of the research and discussion show that there is a significant positive direct effect of work safety on loading and unloading performance, there is a significant positive direct effect of TKBM competence on loading and unloading performance, there is a significant positive direct effect of work safety on loading and unloading productivity, there is a significant positive direct effect of TKBM competence on loading and unloading productivity, there is a significant positive direct effect of performance on loading and unloading productivity, performance is able to mediate work safety on loading and unloading productivity and performance is able to mediate TKBM competence on loading and unloading productivity at Tanjung Priok Port. It is concluded that directly and indirectly, there is an influence of work safety and TKBM competence on performance and its implications for loading and unloading productivity at Tanjung Priok Port.